Three new amides from Streptomyces sp. H7372 - Cheenpracha, Sarot; Borris, Robert P.; Tran, Tammy T.; Jee, Jap Meng; Seow, Heng Fong; Cheah, Hwen Yee; Ho, Coy Choke; Chang, Leng Chee (Sociedade Brasileira de Química, 2011)
Three new amides, methyl phenatate A (1), actiphenamide (2) and actiphenol 1-β-D- glucopyranoside (3), along with thirteen known compounds, were isolated from the organic extract of a fermentation culture of Streptomyces sp. H7372. The structures were elucidated by spectroscopic methods including 1D- and 2D-NMR techniques, and MS analyses. Cycloheximide (6) and cyclo(δAla-L- Val) (8) gave a clear zone of inhibition of Ras-Raf-1 interaction in the yeast two- hybrid assay which showed high potency with 10 and 25 mm clear ZOIs on SD His - and inactive on SD His + at 2.5 μg per disk, respectively.